2018
DOI: 10.1088/1361-6439/aab9d0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic cavitation in microfluidic devices with roughened surfaces

Abstract: The importance of the hydrodynamic cavitation phenomenon in small domains has been increasing during recent decades along with the global demand for microfluidic devices involving small-scale cavitation applications. Different characteristics of microscale hydrodynamic cavitation relative to the conventional size can be exploited in futuristic applications and improvements in the performances of new-generation microfluidic devices. Therefore, in-depth studies on the fundamentals of microscale hydrodynamic cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…He also pointed out different cavitation behaviors attributed to system instabilities, difference in gas content, and surface roughness of the foil. The physical mechanism of the cavity inception is quite complex and somewhat different on scale models and full scale of submerged objects [2][3][4], and also in microsystems [5][6][7][8]. Research has identified the critical velocity for which a sudden change in the desinent cavitation number occurs as an effect of a passing from long to short laminar separation bubbles [9].…”
Section: Introductionmentioning
confidence: 99%
“…He also pointed out different cavitation behaviors attributed to system instabilities, difference in gas content, and surface roughness of the foil. The physical mechanism of the cavity inception is quite complex and somewhat different on scale models and full scale of submerged objects [2][3][4], and also in microsystems [5][6][7][8]. Research has identified the critical velocity for which a sudden change in the desinent cavitation number occurs as an effect of a passing from long to short laminar separation bubbles [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since cavitation may reduce efficiency, generate vibration and acoustic noise, or even cause a catastrophic disaster [12,13], the hydraulic cavitation inside macro machinery has attracted enormous attention from researchers [13,14,15]. Although there are experimental and numerical investigations demonstrating that a microfluidic system with micro-orifices may suffer from the influences of cavitation, there are only a few that concentrate on cavitation inside a microfluidic system until now [16,17,18,19,20,21]. Investigations have mostly focused on explaining the cavitation phenomenon, the effects of turbulent state, and the structural parameters of cavitation characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have mostly focused on explaining the cavitation phenomenon, the effects of turbulent state, and the structural parameters of cavitation characteristics. The principals obtained from macroscale studies may still be applied to a microscale structure [17,18,19,20,21,22,23,24,25,26,27,28,29], however, the turbulent state and scale can affect cavitation characteristics [20].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the roughness on the channel surface led to intensified cavitating flows in comparison with a smooth channel over the same range of flow rate. They also suggested that longer microchannels were suitable for energy harvesting applications because of the penetration of the emerging twin cavities [19]. It should be noted that the entire downstream region of microchannel could be filled with vapor and large vapor bubbles by causing twin cavities, which could be exploited in energy harvesting.…”
Section: Introductionmentioning
confidence: 99%